DONSON and FANCM associate with different replisomes distinguished by replication timing and chromatin domain - Jing Zhang (Nature Communications, 2020)
Eukaryotic replisomes are multiprotein complexes. Here the authors reveal two distinct stressed replisomes, associated with DONSON and FANCM, displaying a bias in replication timing and chromatin domain.